Aberrant configuration of femoral vessels as cause of arterial occlusive disease - Ahuja, Ankit; Naithani, Vinay; Bagara, Amit Kumar; Bhatia, Budhi Prakash (International Surgery Journal, 2018)
Variations in the branching pattern of femoral and profunda femoris arteries have clinical implications while performing various diagnostic imaging procedures as well as during surgeries that are performed in the femoral triangle. Awareness about these variations aid surgeons during preoperative clinical evaluation for surgical and interventional revascularization of the ileo-femoral and femoro-popliteal segments, in open canulation of femoral artery for cardiopulmonary bypass, in radiological interventions for A-V malformations, and in salvage operations for traumatic limb ischemia. Here we report an aberrant configuration of profunda femoris artery which presented as a case of arterial occlusive disease of lower limb. On surgical exploration, Profunda femoris artery was found originating on the medial aspect of left common femoral artery high up in the inguinal region as compared to its usual lower and lateral origin. There was atheromatous occlusion of superficial femoral artery from its origin upto distal femoral metaphysis. In case of occlusion of the superficial femoral artery, the profunda femoris artery forms an effective collateral bed between the ileo-femoral segment and the popliteal artery and its branches. The clinical implications associated with these variations in therapeutic and diagnostic interventions is been discussed along with relevant literature review. Further study is necessary to identify aberrant configuration of femoral vessels as a cause of arterial occlusive disease in the lower limbs.